PENGGUNAAN MULTIMEDIA PEMBELAJARAN BAHASA ARAB BERBASIS APLIKASI MACROMEDIA FLASH 8 DI TPA AL-HIDAYAH SIDOHARJO PRINGSEWU - Sari, Noca Yolanda; Sukmiati, Hermin; Muslihudin, Muhamad (STIT AL MULTAZAM, 2016)
The development of information technology and computers has provided a very significant influence in the development of learning media. The use of multimedia technology as an Arabic learning media is one of the alternatives to help overcome the problem learners learn, because by using multimedia technology, learners are able to learn Arabic independently, more easily, comfortable, and learn according to his ability. Data on observations made on students in field trials, 9 out of 10 students who claimed more easily understand the material with the application of learning using multimedia. Results indicate an increase in learning achievement between before and time using multimedia computer-assisted learning. The percentage that resulted from students' understanding is 90%. Students are more familiar with the material presented by the followers with the appearance, liveliness and material they are important. This research method is library research because the source data comes from written documents and analysis. Macromedia flash-based learning media on learning Arabic language worthy of use as a medium of learning. And this learning media is considered able to increase student's interest and learning value.